The status of Porella subparaphyllina J.S.Lou (Marchantiophyta, Porellaceae), a poorly known species endemic to Yunnan, China - Qian, Kai; Zhu, Rui-Liang (Phytotaxa, 2017)
Porella densifolia (Stephani 1894: 214) Hattori (1944: 20) was first described based on a collection made by the Frenchman P.J.M. Delavay during his expedition to northwestern Yunnan, China. At present Porella densifolia is divided into three subspecies, P. densifolia subsp. densifolia, P. densifolia subsp. andamana Hattori (1969: 346), and P. densifolia subsp. appendiculata Stephani (1910: 301) Hattori (1969: 343) (Söderström et al. 2016). Porella subparaphyllina Lou (1987: 483) is a very rare species known only from its type locality in northwestern Yunnan. Recently we collected many fresh samples from the type localities of both P. subparaphyllina and Porella densifolia subsp. densifolia in northwestern Yunnan. Our examination of the type specimens and recent collections from type localities in Yunnan and other Chinese localities reveal that P. subparaphyllina fits well in Porella densifolia subsp. densifolia. The morphological affinity between P. subparaphyllina and P. densifolia subsp. densifolia is also confirmed by our unpublished molecular data (ITS, trnL-F and rbcL; not shown here) which show that two accessions of Porella subparaphyllina from the type locality are nested within a strongly supported clade with several accessions of typical Porella densifolia subsp. densifolia. Therefore, Porella subparaphyllina is proposed to be conspecific with P. densifolia subsp. densifolia.